Relasi Antara Toleransi dan Sekularisasi dalam Masyarakat Modern - Hery Prasetyo Laoli; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
Tolerance in religion and secularization are contradictory. However, it cannot be denied that both can run alone, because secularization in the absence of tolerance in religion will give rise to immoral attitudes, while tolerance in religion without secularization will only create a constant civilization. The purpose of this study is to find answers to the notion of tolerance and secularization so that a relationship can be found between the two using qualitative research methods based on a literature review approach and this research fully uses library research. The results showed that in the West secularization is placed in an effort to place the potential that exists in humans which is accompanied by the advancement of science without having to be hindered by religious doctrines, so that secularization runs safely. Whereas in the East secularization has always been identified with the contradictory that exists in religion, thus placing its civilization only on the route of stagnation and backwardness due to long-entrenched traditions. In fact, secularization itself is a form of human liberation from religions that are worldly rather than sacred in nature, while tolerance is a view that does not damage the life of modern society which has a lot of secular attitudes, because the teachings of tolerance itself are collective norms that are born into solutions to the history of religious conflicts and beliefs of secular societies. Meanwhile, secularization also needs to embody tolerance in it in order to create a process of mutual understanding and learning between religion and the secular mindset in the modern era. Therefore, tolerance and secularization can bridge harmony and peace in modern society.